2017
DOI: 10.4236/ss.2017.85024
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Surgery of Non-Small Cell Lung Cancer: Evaluation Based on the Questionnaires of Anti-Aging Quality of Life and the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire

Abstract: Background: Patient-reported outcomes of the quality of life (QOL) after an open thoracotomy have not been studied. To determine the physical and mental changes in surgical patients is very important for medical staffs. The surgical patient's satisfaction and overall healthy changes were evaluated by the patient-self assessment questionnaires. Materials and Methods: From July 2007 to April 2008, 26 patients with non-small cell lung cancer (NSCLC) underwent surgical resection. The outcome of the QOL was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For oncological surgery, resection status and survival rates seem to be more of clinical interest. However, more and more studies appeared focussing on quality of life after surgery, showing a decline during short- and long-term follow-up [ 28 30 ]. Different AEs, such as chronic pain, anxiety/depression or general mental function are increasingly moving into focus.…”
Section: Discussionmentioning
confidence: 99%
“…For oncological surgery, resection status and survival rates seem to be more of clinical interest. However, more and more studies appeared focussing on quality of life after surgery, showing a decline during short- and long-term follow-up [ 28 30 ]. Different AEs, such as chronic pain, anxiety/depression or general mental function are increasingly moving into focus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results of the PRO of the surgical treatment [25], the healthy changes suggested that the physical symptoms became worse compared to the menal symptoms. However, in the present study, for the chemotherapeutic modality, the healthy changes suggested that the both physical and mental symptoms became worse.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the PRO of the surgery of lung cancer by an evaluation based on the questionnaires of the anti-aging quality of life (AA-QOL) and EORTC-C30 QLQ [25]. In case of the surgical modality, the healthy changes represented that the physical symptoms became worse compared to the mental symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In such patients, limited wedge resection of the nodule is recommended after evaluation of current imaging studies. Although such thoracic surgeries are rare, they might provide a satisfactory post-operative outcome [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignancies with a very high mortality rate in the world's population. Its early detection and surgical resection are an effective method of treating non-small cell carcinoma in stage I and II, and in some patients in stage IIIA, depending on the pre-operative assessment [8]. Radical resection of lung cancer allows the prolongation of life and improves its quality [9].…”
Section: Introductionmentioning
confidence: 99%